Usages of Mobile Application Developed by Krishi Vigyan Kendra Banavasi - Jayalakshmi, M.; Prasadbabu, G.; Chaithanya, B. H.; Lavanya, A.; Srinivas, T. (Indian Journal of Extension Education, 2021)
A survey was conducted to assess the impact of mobile applications developed by the KrishiVigyan Kendra Banavasi with 150 farmers in Kurnool district of Andhra Pradesh in the year 2020. KVK Banavasi developed three mobile applications namely ANGRAU-ATARI CFLD, ANGRAU Pashu Poshan and Fertilizer Calculator for benefiting farming community. Majority (64.67%) of the respondents were found in medium usage of mobile applications, in agriculture. Fertilizer Calculator mobile application was found highest usage (74.50%) among the farmers when compared with other two applications. ANGRAU ATATRI CFLD application was used by an average of 46.83 per cent farmers for information on new improved varieties, 75 % for control measures of pest and diseases and 29 per cent for market related information. ANGRAU Pashu Poshan application was used by 75 per cent livestock farmers for sheep management, 56 per cent for cattle management and 45 per cent for poultry related information. Fertilizer calculator application was used by 80 per cent farmers for recommended dose of fertilizers and 10 per cent for soil test based fertilizer application.
Keywords: Fertilizer calculator; Impact; Mobile applications; Pashu Poshan